Analisis Perbedaan Abnormal Return Keuangan pada Sektor Consumer Goods Industry Sebelum dan Saat Pengumuman Pandemi COVID – 19 di Bursa Efek Indonesia ( Event Study pada Sub Sektor Food and Beverages dan Sub Sektor Pharmaceuticals periode Februari – April 2020 ) - Teddy Kurnia Dwi Anggoro Kusumo D; Ronny Malavia Mardani; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to analyze whether there are differences in financial abnormal return to the consumer goods industry sector, especially in the food and beverages sub-sector and the pharmaceuticals sub-sector listed on the Indonesia Stock Exchange before and during the right issue. This research was conducted with 2 right issues, the first case of Covid - 19 which occurred on March 2, 2020 and the implementation of the first PSBB by the government on March 30, 2020 with observation periods of 3 days before and 3 days after the announcement respectively. This type of research is an event study using quantitative descriptive methods. Determination of the sample using purposive sampling, with a total sample of 13 food and beverages companies and 7 pharmaceuticals companies. The data used in this study include stock prices, daily closings, stock indexes. The data analysis technique used to answer the research hypothesis was paired sample t-test and Wilcoxon signed ranks test. The results of this study indicate that there is no difference in abnormal returns in the two research sub-sectors before and after the announcement of the first Covid-19 case, while before and after the implementation of PSBB by the government there are differences in abnormal returns in these two subsectors.  Key Words : Right Issue, Financial Abnormal Return, Event Study, Food and Beverages Sub                              Sector and Pharmaceuticals Sub Sector.